Centering prayer’s effects on psycho-spiritual outcomes: a pilot outcome study - Fox, Jesse (Mental health, religion & culture, 2016)
Centering prayer is a spiritual and religious form of meditation grounded in the history of Christian contemplative prayer. Despite its popularity, empirical research investigating centering prayer’s effects on psycho-spiritual outcomes is relative sparse. This pilot outcome study explored the effect of a centering prayer workshop on participants’ (N = 9) depression, anxiety, stress, spiritual transcendence, religious crisis, faith development, and mindfulness. Several significant changes were noted over the course of the six-week study, including decreased anxiety and stress, and increased faith development and mindfulness. Interestingly, we noted that participants likely also experienced a spiritual or religious struggle that follows the established spiritual development paradigm called the Dark Night of the Soul. The study did not include a control group, and so did not account for effects related to history, maturation, or regression to the mean. Nevertheless, the initial results prove promising to develop more sophisticated research programmes that replicate the study’s findings.